Visible-Light Photoredox Catalysis - Xuan, Jun; Xiao, Wen-Jing (Angewandte Chemie International Edition, 2012)
In the last few years, visible‐light initiated organic transformations have attracted increasing attention. The development of visible‐light‐promoted photocatalytic reactions, which enable rapid and efficient synthesis of fine chemicals, is highly desirable from the viewpoint of cost, safety, availability, and environmental friendliness. In this Minireview, recent advances made in this fast developing area of research are discussed. In the spotlight: The title catalysis is an area of research that is developing quickly and has become a powerful and efficient tool in synthetic organic chemistry (see picture, S=Substrates, P=Products). There is little doubt that continued exploration of visible light photoredox catalysis will uncover a wide range of fascinating and useful chemical reactions.